Sport and Exercise Medicine: a misunderstood specialty among medical students and foundation doctors - McGuire, Bonar; Mahfouz, Hassan; Lorenz, Harry; Archer, Edward (International Journal of Medical Students, 2025)
Objectives: To assess medical students’ and foundation doctors’ understanding of Sport and Exercise Medicine (SEM) and SEM careers; to gauge this cohort’s physical activity (PA) level and awareness of PA guidelines. Design and Methods: An anonymised online survey was distributed to medical students and foundation trainees between 28th October 2022 and 20th January 2024. Results: 144 respondents completed the survey. 72.2% were students. 87.5% were aware of SEM. While 98.6% knew that SEM doctors worked with sports teams, only 45.8% knew that they served the general population. Fewer than half of respondents (43.7%) knew that SEM specialty training existed. 22.2% were considering pursuing SEM careers, but only one respondent expressed an interest in exercise medicine. Only 29.2% knew that there were SEM posts in the NHS, and 11.1% believed that SEM was an entirely independent-sector specialty. Most respondents (62.5%) achieved the recommended minimum weekly aerobic PA target, with similar rates among students (62.7%) and foundation doctors (61.5%). 83.3% indicated that their PA level was limited by study or work commitments. Respondents performed no better than chance at identifying the minimum weekly aerobic exercise target recommended in the UK guidelines (26.4% vs 20%, p=0.055). Conclusions: Although there is interest in SEM among medical students and foundation doctors, there is a lack of understanding of the role of SEM doctors and of the availability of SEM specialty training. This cohort was unfamiliar with PA guidelines and was slightly less physically active than the national average.